A Study of Uttar Pradesh's Regional Political Parties Emerge (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Uttar Pradesh is sometimes considered the political epicentre of India, and this research looks at how regional political parties there came to be and what effect they had. Caste, religion, and socioeconomic position are some of the sociopolitical aspects that are investigated in relation to the dynamics of political mobilisation within the state. In Uttar Pradesh, regional political parties are very important since they represent local interests and help shape policy, especially when it comes to fighting for the rights and dreams of under-represented communities. A multi-party system that reflects the state's varied socio-cultural fabric has replaced a single-party supremacy in Uttar Pradesh's party system throughout the years. The article also takes into account the impact of notable groups like the Yadavs and Muslims, the consequences of mobilisation based on caste, and the emergence of political movements that challenge established power systems. In the end, this research highlights how regional parties play a crucial role in encouraging representation and balancing power within India's larger political system.